Impact of cancer-related fatigue on quality of life in patients with cancer: multiple mediating roles of psychological coherence and stigma - Jiashuang Xu; Qiang Li; Ziyun Gao; Pengjuan Ji; Qiqi Ji; Miaojing Song; Yian Chen; Hong Sun; Xin Wang; Lin Zhang; Leilei Guo (BMC Cancer)
Abstract Objective The goal of this current research was to explore the impact of cancer-related fatigue on the quality of life among patients with cancer, as well as the multiple mediating roles of psychological coherence and stigma. Methods This study utilized a cross-sectional design. A questionnaire was administered between November 2022 and May 2023 to 364 patients with cancer in two tertiary hospitals in Jinzhou City, Liaoning Province, China. The questionnaires included the General Information Questionnaire, Cancer-Related Fatigue Questionnaire, Psychological Coherence Scale, Stigma Scale, and Quality of Life Questionnaire. SPSS 25.0 and PROCESS 3.5 macros were used for descriptive statistics and correlation analysis of the data, as well as multiple mediation effect tests. Results Cancer-related fatigue directly affects quality of life (β = -0.950, 95% CI = -1.138 to -0.763) and indirectly through three mediators: psychological coherence (β = -0.172, 12.58% of total effect), stigma (β = -0.193, 14.12% of total effect), and both psychological coherence and stigma (β = -0.052, 3.80% of total effect), totaling a 30.50% mediating effect. Conclusion Overall, psychological coherence and stigma may play an important mediating role between cancer-related fatigue and quality of life in patients with cancer. This suggests that alleviating cancer-related fatigue, while enhancing psychological coherence and reducing stigma, could be effective strategies for improving patients’ quality of life. Therefore, healthcare professionals and related professionals should pay attention to and adopt effective interventions to alleviate cancer-related fatigue, enhance psychological coherence, and reduce stigma, thereby contributing to the overall well-being and quality of life of patients with cancer.